2014
DOI: 10.1128/aem.03150-13
|View full text |Cite
|
Sign up to set email alerts
|

Culture Volume and Vessel Affect Long-Term Survival, Mutation Frequency, and Oxidative Stress of Escherichia coli

Abstract: Bacteria such as Escherichia coli are frequently studied during exponential-and stationary-phase growth. However, many strains can survive in long-term stationary phase (LTSP), without the addition of nutrients, from days to several years. During LTSP, cells experience a variety of stressors, including reactive oxidative species, nutrient depletion, and metabolic toxin buildup, that lead to physiological responses and changes in genetic stability. In this study, we monitored survival during LTSP, as well as re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 36 publications
4
48
0
Order By: Relevance
“…For example, depending on the specific drug being assayed, we observe between 1-4 logs of killing, which can be perturbed by extrinsic factors such as the level of aeration and availability of terminal electron acceptors. Interesting recent work has illustrated that phenotypes such as cell death, mutagenesis, oxidative stress, and related activation of OxyR can all be reduced, depending on the method of culturing (101). These findings are consistent with a recent commentary on the current ROS debate (93), which suggested that differences in experimental conditions may help explain the incongruent conclusions regarding the ROS hypothesis reached by others based on the absence or minimal extent of such phenotypes (49)(50)(51).…”
Section: Discussionsupporting
confidence: 79%
“…For example, depending on the specific drug being assayed, we observe between 1-4 logs of killing, which can be perturbed by extrinsic factors such as the level of aeration and availability of terminal electron acceptors. Interesting recent work has illustrated that phenotypes such as cell death, mutagenesis, oxidative stress, and related activation of OxyR can all be reduced, depending on the method of culturing (101). These findings are consistent with a recent commentary on the current ROS debate (93), which suggested that differences in experimental conditions may help explain the incongruent conclusions regarding the ROS hypothesis reached by others based on the absence or minimal extent of such phenotypes (49)(50)(51).…”
Section: Discussionsupporting
confidence: 79%
“…Monitoring cell growth, survival, culture pH, and mutation frequency. To monitor cell growth and survival, viable cell counts were determined by serial dilution of cells sampled periodically from the cultures, followed by plating on LB agar (2,25). The limit of detection in all experiments was Ͼ1,000 CFU/ml (25).…”
Section: Methodsmentioning
confidence: 99%
“…Enzyme-linked immunosorbent assays (ELISAs) were performed as previously described (2). Briefly, 50 l of whole-cell lysate (protein concentration, 0.5 to 1.0 mg/ml) were loaded into standard polystyrene 96-well plates (Corning, Inc.) with 100 l sodium carbonate binding buffer and incubated overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations